Die Dialektik der Angewiesenheit: Das sozialpolitische Werk von Eduard Heimann neu lesen - Böhnisch, Lothar (transcript, 2020)
Eduard Heimann's model of the »dialectic of dependence« rediscovered and made fruitful for social policy, the sustainability discourse and the neo-socialist discussion.